Resposta do Abacaxizeiro 'Vitória' a Doses de Nitrogênio em Solos de Tabuleiros Costeiros da Paraíba - da Silva, André Luiz Pereira [UNESP]; da Silva, Alexandre Paiva; de Souza, Adailson Pereira; Santos, Djail; de Melo Silva, Silvanda; da Silva, Valéria Borges (FapUNIFESP (SciELO), 2012)
Informations about fertilization and mineral nutrition of the new fusariosis-resistant pineapple cultivars are still scarce, despite the importance of this crop. The purpose of this study was to evaluate the effect of increasing doses of N on fruit yield and quality of the pineapple cultivar 'Vitória' grown on a 'Humilúvico Espodossolo' in the region of Tabuleiros Costeiros, in the state of Paraíba. The experiment was arranged in a randomized block design, using five N doses (100, 200, 300, 500 and 600 kg ha-1N, as urea) applied 60, 180 and 270 days after planting (dap) with three replications. The following variables were evaluated: length and fresh matter of the 'D' leaf; contents of N, P and K in the portions with and without chlorophyll, 300 and 420 dap; average weight, yield, physical properties (fruit weight, length and medium diameter; crown weight and length) and chemical properties (pH, soluble solids -SS, titrable acidity - AT, and the SS/AT ratio) of the fruits at harvest. Increasing N doses linearly increased length and fresh matter of the 'D' leaf and N content and decrease both P and K contents of the chlorophyll portion 300 dap, but did not affect nutrient contents 420 dap; in the chlorophyll-free portion. Increasing N doses, also, led to an increase in K contents 320 dap, but to reductions 420 dap. Individual fruit weight and total yield increased with increasing N doses, as maximum values of 1.0 kg and 37.9 t ha-1 were estimated at doses of 409.0 and 439.0 kg ha-1 N, respectively. The N doses did not affect the fruit quality properties, which were compatible with the characteristics described for this cultivar.
Response of 'Vitória' Pineapple to nitrogen in coastal tablelands in Paraiba
Keywords: Ananas comosus comosus L.; Fusariosis; Nitrogenous fertilization